Perceptions, meanings and constructions of `security` before Euro 2020 - Ludvigsen, J. (Liverpool John Moores University, 2021)
In a post-9/11 world, `security` and `security governance` have become increasingly central to the hosting of sport mega-events (SMEs). Currently, security operations at contemporary SMEs constitute some of the largest security operations in the world. In recent years, one can observe a growing academic engagement with the social and spatial effects of SME securitizations. Still, researchers agree that there is a need for more critical engagement with event-specific security strategies and governance, and examinations of what `security` means in a SME context. This thesis provides an examination of the meanings, perceptions and constructions of `security` before the 2020 The Union of European Football Associations (UEFA) European Football Championship (Euro 2020). This SME was assigned a historical format. For the first time in history, 12 European countries shared the hosting rights for the tournament originally to be staged in June and July 2020. Such novel hosting format raised a series of new questions speaking to mega-event securitizations. Then, in light of the global coronavirus disease 2019 (COVID-19) pandemic, further questions emerged and intensified as Euro 2020 was provisionally postponed for 12 months, in March 2020, on `health` and `safety` grounds. In global sports, Euro 2020 therefore symbolized an extraordinary and historical SME from a security outlook. In this thesis, I argue that in a society increasingly preoccupied with `security` and `risk`, Euro 2020`s security planning - aiming to protect the geographically unique event - proves an exemplary and powerful empirical site for broader transnational and precautionary practices of security governance in the present-day world. Whilst these driving forces have appeared in existing research on SMEs, the reality is that each SME possesses unique local characteristics and contexts which they are planned and delivered within. Such claim comes particularly true in relation to Euro 2020`s multi-national format. In addition to ensuring `safe` or `secure` events, accounting for the (ever-)changing dynamics in the international system, the thesis also records how these underpinning processes tie firmly into commercial and sanitizing processes that are brought together by security-related policies. To explain the construction of `security`, my thesis introduces a new framework - the `troika of security` - through which SME `security` can be understood. Drawing from qualitative methods, including stakeholder interviews, policy documents and media sources, this thesis provides an in-depth investigation into the `security` pre-planning before Euro 2020. It also captures the unfolding events as COVID-19 resulted in the collapse of European-wide sporting events. The thesis critically unpacks what `security` in a SME context means, can mean, and how it is reconfigured. Overall, this thesis makes sociological sense of the processes through which `security` was to be constructed in Euro 2020`s case. Thereby, it contributes to the field with the most comprehensive study to date, on Euro 2020`s extraordinary pre-event securitization. It also adds to the existing knowledge with one of the first studies that critically interrogates COVID-19 as a `security threat` both in a general sense and as situated in global sports.